The Impact of the Soviet Heritage on Women’s Political Leadership in Modern Russia - Tatyana A. Ivleva (RUDN Journal of Public Administration, 2024)
The study analyzes the specifics of women’s political leadership in the USSR and identifies the factors that predetermined the secondary role of women in Soviet, and later modern Russian politics. The purpose of this study is to identify the features of women’s activities as political leaders in the Soviet state and compare them with the features of women’s participation in political power in modern Russia. To achieve the goal, historical-chronological and comparative analysis are used as research methods. The unique experience of the women’s departments is considered in detail, as well as the personal factor of Soviet women leaders as the reason for political success. It is concluded that during the entire existence of the Soviet Union, the parity ratio of men and women at any level of power was not achieved even despite attempts to introduce various measures, such as a quota system, to achieve this goal. However, among the reasons for this situation, it was highlighted that attempts to achieve gender parity in government were primarily ideological in nature and aimed not at achieving real equality, but at demonstrating the ideology of the USSR on the world stage. The presence of women in the highest government positions in the USSR was an extremely rare phenomenon, since, in order to meet practical needs, the state, as a rule, preferred to involve women in politics at the lowest levels of the political hierarchy. A comparative analysis of women’s political leadership in the Soviet period with the present has shown that the same trend persists in modern Russia.